Acute fibrinous and organising pneumonia: a rare histopathological variant of chemotherapy-induced lung injury. (6th April 2016) - Gupta, Arjun; Sen, Shiraj; Naina, Harris
Abstract : Bleomycin-induced lung injury is the most common chemotherapy-associated lung disease, and is linked with several histopathological patterns. Acute fibrinous and organising pneumonia (AFOP) is a relatively new and rare histological pattern of diffuse lung injury. We report the first known case of bleomycin-induced AFOP. A 36-year-old man with metastatic testicular cancer received three cycles of bleomycin, etoposide and cisplatin, before being transitioned to paclitaxel, ifosfamide and cisplatin. He subsequently presented with exertional dyspnoea, cough and pleuritic chest pain. CT of the chest demonstrated bilateral ground glass opacities with peribronchovascular distribution and pulmonary function tests demonstrated a restrictive pattern of lung disease with impaired diffusion. Transbronchial biopsy revealed intra-alveolar fibrin deposits with organising pneumonia, consisting of intraluminal loose connective tissue consistent with AFOP. The patient received high-dose corticosteroids with symptomatic and radiographic improvement. AFOP should be recognised as a histopathological variant of bleomycin-induced lung injury.